Ophthalmological practices in COVID pandemic during first and second wave: Learnings and new beginnings - Vivek Singh; Abhishek Anand; Vidya Bhushan Kumar; Shadma Eqbal; Pragati Raj (Wolters Kluwer -Medknow Publications, 2022)
Purpose: TO study the impact of covid 19 in a tertiary eye care hospital. Study type: single centre retrospective observational study. Method: Novel corona virus "COVID-19" is now an established global Pandemic. Index case of Novel Corona virus "COVID-19" virus was first reported from Wuhan, People's Republic of China on 31 December 2019. Bihar with a population of 120 million is one of the most densely populated and least developed states in India. With 1 doctor/29,000 persons and1 hospital bed/8,645 people, it was expected to be one of the worst hit state in COVID-19 pandemic. All patient visiting an ophthalmologist were seen with full precaution and with a practical Standard Operating Protocol (SOP), advised by World Health Organization (WHO), Centre for disease control (CDC), MOHFW, American Academy Of Ophthalmology(AAO) and All India Ophthalmological Society(AIOS). Patient visiting and treatment protocol followed in a tertiary care hospital were analysed. Results: 3617(2432 males ,1185 females) new patients and 3145(2149 males, 996 females) old/follow up patients visited RIO OPD from lockdown (25 march 2020) till unlock 4(30 September, 2020) which is about 85.41% decrement in comparison to last year in same period 21747(13335 males, 8412 females) new patients and 24610(15508 males, 9102 females). Conclusion: Proper use of n95 masks, gloves, caps, face shield, PPE kit while examining patients and operating them were few important precautions. Regular use of sanitizer, hand washing, minimizing patient doctor contact time, minimal hospital stays, use of artificial intelligence are few other ways practiced to prevent exposure to COVID 19. This pandemic has taught us a lot about people unity cooperation, what is important in life, ophthalmologically tele-ophthalmology will play a big role in future an evident in this pandemic.